2017
DOI: 10.1186/s12936-017-1850-8
|View full text |Cite
|
Sign up to set email alerts
|

Global survey of malaria rapid diagnostic test (RDT) sales, procurement and lot verification practices: assessing the use of the WHO–FIND Malaria RDT Evaluation Programme (2011–2014)

Abstract: BackgroundMalaria rapid diagnostic tests (RDTs) play a critical role in malaria case management, and assurance of quality is a key factor to promote good adherence to test results. Since 2007, the World Health Organization (WHO) and the Foundation for Innovative New Diagnostics (FIND) have coordinated a Malaria RDT Evaluation Programme, comprising a pre-purchase performance evaluation (product testing, PT) and a pre-distribution quality control of lots (lot testing, LT), the former being the basis of WHO recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 8 publications
0
32
0
Order By: Relevance
“…Since malaria RDTs became available in the 1990s, growth in the number of tests, manufacturers, and volumes sold has been exponential ( 25 , 26 ). In parallel, the proportion of fever case-patients having access to diagnostic services before treatment has also expanded, particularly in Africa, largely attributed to the implementation of HRP2-based malaria RDTs ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since malaria RDTs became available in the 1990s, growth in the number of tests, manufacturers, and volumes sold has been exponential ( 25 , 26 ). In parallel, the proportion of fever case-patients having access to diagnostic services before treatment has also expanded, particularly in Africa, largely attributed to the implementation of HRP2-based malaria RDTs ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…The matureness level of some malaria RDTs is quite high, and some of the tests are in the WHO recommendation list [ 29 ]. They are fast, cheap, easy-to-use, and mass producible, which justifies their broad use [ 30 ], and the reason why such tests will not be replaced by other techniques, especially for triage tests at remote sites (RDT manufacturers’ reports showed that RDT sales had more than doubled from 2011 to 2014 [ 30 ]). Yet, a major drawback of RDTs is that each test targets only one disease and, although typically the first RDT is given for malaria, in case of malaria-negative result, other RDTs have to be sought or other analyses to be done.…”
Section: Diagnosticsmentioning
confidence: 99%
“…Since its development in the 1990s, and with more than 200 currently available brands, there has been consistent reports of observable increase in malaria RDT sales worldwide [9,10]. Most of the malaria RDTs exploit the presence of P. falciparum Histidine-Rich Protein-2 (PfHRP2) for the detection of Plasmodium falciparum [11].…”
Section: Introductionmentioning
confidence: 99%